Influence of dispersants on aging and frost elastomeric compositions based on butadiene acrylonitrile rubbers - R. M. Dolinskaya (Vestnik Voronežskogo Gosudarstvennogo Universiteta Inženernyh Tehnologij, 2016)
The possibility of use of dispergators of various nature for production of rubber technical products with expanded temperature conditions of operation is studied. It is investigated influences of dispergators of Dispergator FL and INT 159 on properties of rubber mixes for receiving products with high resistance to thermal aging or frost resistance. Research of influence of modifiers was conducted for rubber mixes on the basis of butadienenitrile rubbers synthetic (BNRS)-18 and BNRS-28. I’s established that at addition of a dispergator of Dispergator FL the indicator of relative deformatstion of compression (RDC) and respectively heat stability of rubbers increases. Introduction to structure of elastomeric composition of a dispergator of INT 159 practically doesn’t influence frost resistance, and Dispergator FL worsens her (the coefficient of frost resistance decreases by 15.4–17.8%). Possibly it is connected with the fact that at the lowered temperatures in the presence of Dispergator FL there is a bigger delay of relaxation processes and decrease in energy of the thermal movement of links of macromolecules of rubbers. It becomes insufficient for overcoming of intermolecular interaction in the modified system and commission of conformational transitions of macromolecules under the influence of external loading. Mechanical energy is to a large extent mentioned not on change of a form of macromolecules, and on their mechanodestruction. However, it increases heat stability since it that is higher, than molecular mobility is lower. INT 159 dispergator components, settling down on borders of supramolecular formations of elastomers, increase mobility of links of macromolecules of rubbers, weaken chemical bonds in them, reduce thermal stability, but at the same time INT 159 dispergator practically doesn’t reduce frost resistance therefore it is expedient to apply it when receiving frost-resistant elastomeric composition. Thus, when receiving thermostable elastomeric compositions it is necessary to use Dispergator FL, and frost-resistant – INT 159 dispergator.